2019
DOI: 10.1108/qae-11-2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and staff perceptions of vocational education institution heads’ virtues

Abstract: Purpose The relevance of institution leaders’ personal qualities for providing quality education is widely recognized. The purpose of this paper is to explore vocational education and training (VET) institution leaders’ character features. The research question was twofold: What are the features of the character of the pedagogical leaders of three Latvian VET institutions according to students, teachers and institution board members? What are the differences between respondents’ groups regarding their percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, not all the agents involved always have the same perception of the characteristics of leadership. As can be seen from the results of the study carried out by Fernández-González et al (2020), there are significant differences between the perceptions of the leadership characteristics of students and university staff. While staff members particularly appreciate the performance and intellectual virtues of leaders, to students, the moral virtues of the directorial staff are more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all the agents involved always have the same perception of the characteristics of leadership. As can be seen from the results of the study carried out by Fernández-González et al (2020), there are significant differences between the perceptions of the leadership characteristics of students and university staff. While staff members particularly appreciate the performance and intellectual virtues of leaders, to students, the moral virtues of the directorial staff are more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also confi rm the low character quality in other aspects by revealing that students' independence in learning has not been maximally encouraged (Wiyati, 2021). It is also followed by the integrity of students who are also low during the learning process (Fernández González, Pīgozne, Surikova, & Vasečko, 2020). Meanwhile, even though the students' cooperation is good enough, it needs to be reformed (Wiyati, 2021).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…These findings echoed the importance of school leaders' ethical stance and personal example stressed in recent research (Boydak Özan et al, 2017;Chan et al, 2019;Walker et al, 2017). Recent research has found that the principal's moral role model seems to be particularly relevant for students (Fernández González et al, 2019).…”
Section: Reflection and Communicationmentioning
confidence: 99%